Catalase as a Molecular Target for Male Infertility Diagnosis and Monitoring: An Overview - Nuria Rubio-Riquelme; Natalia Huerta-Retamal; María José Gómez-Torres; Rosa María Martínez-Espinosa (MDPI AG, 2020)
Catalase (CAT) stands out as one of the most efficient natural enzymes when catalysing the split of H2O2 into H2O and O2; H2O2 is one of the reactive oxygen species (ROS) involved in oxidative stress, a process closely related to aging and several health disorders or diseases like male infertility. Some studies have correlated H2O2 with male infertility and catalase with fertility restoration. However, the number of studies conducted with human beings remains scarce. Considering the use of CAT as a molecular target for biochemical analysis, this review summarises the current knowledge on how CAT influences human beings’ male fertility. Thus, three different databases were consulted—Scopus, PubMed and WOS—using single keywords and combinations thereof. A total of 40,823 articles were identified. Adopting inclusion and exclusion criteria, a final database of 197 articles served to conduct this work. It follows from this analysis that CAT could play an important role in male fertility and could become a good target for male infertility diagnosis and monitoring. However, that potential role of CAT as a tool in diagnosis must be confirmed by clinical trials. Finally, guidelines are suggested to reinforce the use of CAT in daily clinical tests for male fertility diagnosis and monitoring.